2010
DOI: 10.1158/1535-7163.mct-10-0673
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1B1 Gene Polymorphisms as Predictors of Anticancer Drug Activity: Studies with In vitro Models

Abstract: Cytochrome P450 1B1 (CYP1B1) is found in tumor tissue and is suspected to play a role in oncogenesis and drug resistance. CYP1B1 gene polymorphisms have been associated with the risk of developing lung and other cancers. They may be associated with tumor response to anticancer drugs. We have determined 4 frequent nonsynonymous gene polymorphisms of CYP1B1 in the human tumor cell lines panels of the National Cancer Institute (NCI) and the Japanese Foundation for Cancer Research (JFCR): rs10012 (R48G), rs1056827… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…CYP1B1 belongs to cytochrome p450 family, which is a multi-gene family of enzymes implicated in the metabolism of a diverse range of xenobiotics and endogenous compounds (24). Several researchers have proposed interesting concepts, in explaining the mechanisms of CYP1B1 induced cytotoxic effect reduction of chemotherapeutic drug (20,21,23,25), as other have mainly focused on CYP1B1 polymorphism in cancer process (22,32,33). Of particular interest, Patel et al reported that CYP1B1 may be regulated by cytokines, as interleukin-6 was observed to mediate of CYP1B1 upregulation via DNA methylation in colorectal cancer (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP1B1 belongs to cytochrome p450 family, which is a multi-gene family of enzymes implicated in the metabolism of a diverse range of xenobiotics and endogenous compounds (24). Several researchers have proposed interesting concepts, in explaining the mechanisms of CYP1B1 induced cytotoxic effect reduction of chemotherapeutic drug (20,21,23,25), as other have mainly focused on CYP1B1 polymorphism in cancer process (22,32,33). Of particular interest, Patel et al reported that CYP1B1 may be regulated by cytokines, as interleukin-6 was observed to mediate of CYP1B1 upregulation via DNA methylation in colorectal cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 promotes cisplatin resistance through upregulation of CYP1B1. Increasing evidence has shown that many cytotoxic drugs are metabolized by cytochrome p450 (CYP) enzymes (17)(18)(19)(20)(21)(22)(23)(24)(25), we therefore explored the correlation of CXCR4 with CYP-related molecules (CYP1A1, CYP1A2, CYP1B1, CYP2C8, CYP2C9, CYP2C18, CYP2C19, CYP2E1, CYP3A4, CYP3A5, CYP3A7 and CYP3A43) by bioinformatics (Table II). Our results indicated a positive correlation between CXCR4 and CYP1B1 with r= 0.616 (P<0.0001) and r= 0.538 (P<0.0001) in GSE30219 and GSE41271 datasets, respectively ( Fig.…”
Section: Cxcr4 Knockdown Enhances Cisplatin-induced Apoptosis and Inhmentioning
confidence: 99%
“…6,7 CYP1B1 gene polymorphisms and dysregulated CYP1B1 expression have been associated with the risk of developing lung and other cancers, 8,9 primary congenital glaucoma, 10 and systemic hypertension. 11 Multiple lines of evidence from both human and mouse show a role for CYP1B1 in the development of PAH.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies conducted on the CYP1B1 enzyme have indicated that the polymorphisms of this gene can change the enzymatic activity and the catalytic features of the enzymes (27,28). Considering four polymorphisms in the codon of Arg48Gly (CYP1B1*1), Ala119Ser (CYP1B1*2), Leu432Val (CYP1B1*3) and Asn453Ser (CYP1B1*4), it becomes clear that they have more hydroxylation activity than normal types, and all of them are related to the susceptibility of developing a cancer (27,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%